2016
DOI: 10.3390/brainsci6030021
|View full text |Cite
|
Sign up to set email alerts
|

DBS for Obesity

Abstract: Obesity is a chronic, progressive and prevalent disorder. Morbid obesity, in particular, is associated with numerous comorbidities and early mortality. In patients with morbid obesity, pharmacological and behavioral approaches often have limited results. Bariatric surgery is quite effective but is associated with operative failures and a non-negligible incidence of side effects. In the last decades, deep brain stimulation (DBS) has been investigated as a neurosurgical modality to treat various neuropsychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 83 publications
(97 reference statements)
0
16
0
1
Order By: Relevance
“…We did find a trend towards a decline in BMI in the subgroup of patients with (morbid) obesity, but we did not see a replication of the substantial weight loss previously described [1]. The vALIC is currently being explored as a potential target for DBS in obesity for its assumed role in reward-related behavior [4,5,6]. Evidence for the involvement of the NAc/vALIC in compulsive eating and obesity is limited to preclinical studies that show low D2-binding in the striatum in obese individuals after food-related sensory stimuli, and in animal studies that show reduced caloric intake and weight loss associated with an upregulation of the D2 receptor.…”
Section: Discussionmentioning
confidence: 86%
“…We did find a trend towards a decline in BMI in the subgroup of patients with (morbid) obesity, but we did not see a replication of the substantial weight loss previously described [1]. The vALIC is currently being explored as a potential target for DBS in obesity for its assumed role in reward-related behavior [4,5,6]. Evidence for the involvement of the NAc/vALIC in compulsive eating and obesity is limited to preclinical studies that show low D2-binding in the striatum in obese individuals after food-related sensory stimuli, and in animal studies that show reduced caloric intake and weight loss associated with an upregulation of the D2 receptor.…”
Section: Discussionmentioning
confidence: 86%
“…The technical problems with stimulating device in this patient were uncontrolled periods of switching the stimulator off, which needed correction during follow-up visits (27). Other experiences with deep brain stimulation for obesity are very limited (26). This modality of treatment, even though present results are modest, …”
Section: Deep Brain Neuromodulation (Figure 7)mentioning
confidence: 81%
“…Since neurophysiological studies have shown that nucleus accumbens is responsible for rewarding (happy feeling) after eating, it became a target of deep brain stimulation (26). A report on a single patient with bilateral implantation of stimulating electrodes into nucleus accumbens in a 19-year-old girl, suffering from obesity as a result of hypothalamus insufficiency after craniopharyngioma removal.…”
Section: Deep Brain Neuromodulation (Figure 7)mentioning
confidence: 99%
“…Obese animals receiving NAc shell stimulation had a reduction in weight gain 22 associated with increased dopamine levels and the upregulation of D2 receptors. 10 , 22 Reductions in binge eating have also been documented in rodents receiving NAc core 23 and NAc shell stimulation, 24 the latter effect being mitigated by D2 receptor antagonists.…”
Section: Discussionmentioning
confidence: 95%